Menyoal Dekonstruksi Keadilan Sahabat: Kritik atas Muhammad Tahir Alibe - Shidqon, Alfan; Rifqa, Zakiyan (El-Sunan: Journal of Hadith and Religious Studies, 2023)
This article provides a review of 'Adalah al-Shahabah Kepada Rekonstruksi Definisi Sahabat: Kajian Kritis Mengenai Sahabat dalam Tinjauan Nas by Muhammad Tahir Alibe. In the article, Tahir presents two main points: a redefinition of the term "companions" and a rejection of the "all companions are fair" rule in hadith sanad criticism. The review in this article focuses on three key issues: Firstly, the negative portrayal of the history of the Companions. Secondly, the analysis of arguments supporting and opposing the fairness of the Companions. Thirdly, a critical assessment of the redefined term "companions." To accomplish these objectives, this article employs a comparative literature-based research approach. The findings of this review reveal: Firstly, the historical narrative of the Companions in Tahir's article demonstrates bias. Secondly, the mapping of pro and con arguments lacks balance. Thirdly, the proposal to redefine the term "sahabat" requires further examination. ABSTRAK Artikel ini berisi ulasan atas Dekonstruksi ‘Adalah al-Shahabah Kepada Rekonstruksi Definisi Sahabat: Kajian Kritis Mengenai Sahabat dalam Tinjauan Nas oleh Muhammad Tahir Alibe. Dalam artikel tersebut, Tahir menawarkan dua hal: pendefinisian ulang istilah sahabat dan penolakan atas kaidah “semua sahabat adil” dalam kritik sanad hadis. Ulasan dalam artikel ini berfokus pada tiga persoalan: Pertama, narasi negatif sejarah sahabat. Kedua, pemetaan argumentasi pro dan kontra terhadap keadilan sahabat. Ketiga, tinjauan kritis atas pendefinisian ulang istilah sahabat. Guna mencapai maksud tersebut, artikel ini menggunakan riset pustaka berbasis komparasi. Hasil dari ulasan ini menunjukkan: Pertama, narasi sejarah sahabat dalam artikel Tahir mengandung bias. Kedua, pemetaan argumentasi pro dan kontra kurang berimbang. Ketiga, tawaran pendefinisian ulang istilah sahabat perlu ditinjau ulang.